New Orleans con Sabor Latino : The History and Passion of Latino Cooking - Cuadra, Zella Palmer (Book collections on Project MUSE., 2013)
"New Orleans con Sabor Latino is a documentary cookbook that draws on the rich Latino culture and history of New Orleans by focusing on thirteen New Orleanian Latinos from diverse backgrounds. Their stories are compelling and reveal what for too long has been overlooked. The book celebrates the influence of Latino cuisine on the food culture of New Orleans from the eighteenth century to the influx of Latino migration post-Katrina and up to today. From farmers' markets, fine-dining restaurants, street cart vendors, and home cooks, there isn't a part of the food industry that has been left untouched by this fusion of cultures. Zella Palmer Cuadra visited and interviewed each creator. Each dish is placed in historical context and is presented in full-color images, along with photographs of the cooks. Latino culture has left an indelible mark on classic New Orleans cuisine and its history. and now this contribution is celebrated and recognized in this beautifully illustrated volume. The cookbook includes a lagniappe (something extra) section of New Orleans recipes from a Latin perspective. Such creations as seafood paella with shrimp boudin, Puerto Rican po'boy (jibarito) with grillades, and Cuban chicken soup bring to life this delicious mix of traditional recipes and new flavors"--